2021
DOI: 10.1063/5.0031821
|View full text |Cite
|
Sign up to set email alerts
|

The photophysics of Ruddlesden-Popper perovskites: A tale of energy, charges, and spins

Abstract: Quasi two-dimensional halide perovskites (also known as Ruddlesden-Popper or RPs) are the most recent and exciting evolution in the perovskite field. Possessing a unique combination of enhanced moisture and material stability, whilst retaining the excellent optoelectronic properties, RPs are poised to be a game changer in the perovskite field. Spurred by their recent achievements in solar cells, light-emitting diodes and spintronic devices, these materials have garnered a mounting interest. Herein, we critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 171 publications
0
66
0
Order By: Relevance
“…[21] Such energetic disorder is proposed as a possible cause of the differences in the reported dynamics of the energy cascade. [16] In the context of average excess energy loss of carriers, the coherent process will facilitate sub-ps localization of carriers into high-n QWs (out-competing extraction, that we estimated previously to be of the order of tens of ps) where BCP can no longer extract them. We performed 2DES for the two RPP systems to probe such ultrafast dynamics.…”
Section: Probing the Effect Of Organic Spacer With Two-dimensional El...mentioning
confidence: 98%
See 1 more Smart Citation
“…[21] Such energetic disorder is proposed as a possible cause of the differences in the reported dynamics of the energy cascade. [16] In the context of average excess energy loss of carriers, the coherent process will facilitate sub-ps localization of carriers into high-n QWs (out-competing extraction, that we estimated previously to be of the order of tens of ps) where BCP can no longer extract them. We performed 2DES for the two RPP systems to probe such ultrafast dynamics.…”
Section: Probing the Effect Of Organic Spacer With Two-dimensional El...mentioning
confidence: 98%
“…RPP are layered materials, where alternate octahedron perovskite and large organic cation layers form QWs with strong confinement in the z-dimension. [16] The unique structure of mixed-phase RPP films presents another lever for tailoring Harvesting the excess energy from absorbed above bandgap photons is a promising approach to overcome the detailed balance limit for higher solar cell efficiencies. However, this remains very challenging for 2D layered halide perovskites as the fast excess energy loss competes effectively with charge extraction.…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that the domain distribution is a key factor determining the energy funneling degree. [53] The amplitude of 734 nm PB band is weak due to the low content of n ¼ 8 domains. Nevertheless, the 734 nm band can be distinguished unambiguously.…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact mechanism in details for the funneling process is yet unclear until now. [10,[46][47][48][49][50][51][52][53] Förster resonance energy transfer (FRET) and Dexter-type charge transfer (CT) via carrier diffusion are proposed to explain the energy funneling. [38,[54][55][56] The FRET model suggests that the energy resonantly transfers from large-bandgap grains to grains with narrower bandgaps through dipole-dipole coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) Ruddlesden-Popper (RP) perovskites have recently drawn ever-increasing attention for their unique characteristics of great quantum confinement effect, large exciton binding energy, and improved stability. [25][26][27] Some more recent studies have revealed that Cs 2 PbI 2 Cl 2 is an inorganic 2D perovskite with the typical RP phase. 28,29 Furthermore, many appealing optoelectronic properties, including high carrier mobility, a direct bandgap, small carrier effective masses, a low exciton binding energy, and excellent ambient/thermal stability have been identified for it.…”
Section: Introductionmentioning
confidence: 99%